2002
DOI: 10.1128/jb.184.23.6410-6416.2002
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Properties of Neisseria gonorrhoeae LgtE

Abstract: A fragment of chromosomal DNA encoding the lgtE gene of Neisseria gonorrhoeae strain F62 was amplified by PCR and cloned into the expression vector pET15b. Functional LgtE was purified and its biochemical properties were determined. The purified enzyme was maximally active in buffer containing manganese; minimal activity was obtained in buffer containing other divalent cations. LgtE was only able to mediate the addition of UDP-galactose into neisserial lipooligosaccharides (LOSs). We used a variety of genetica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Genetic studies on LOS biosynthesis in strain F62 identified a gene cluster lgtA-E (10) that was responsible for the addition of most of the sugars found on the ␣ chain. Biochemical and genetic analysis have confirmed the functions of each of these genes (3,24,38,40) and their involvement in the synthesis of the ␣ chain. Additional genes needed to synthesize the ␤ and ␥ chain have also been identified (1,18), and most of the biochemical properties of these gene products have been defined (41).…”
mentioning
confidence: 84%
“…Genetic studies on LOS biosynthesis in strain F62 identified a gene cluster lgtA-E (10) that was responsible for the addition of most of the sugars found on the ␣ chain. Biochemical and genetic analysis have confirmed the functions of each of these genes (3,24,38,40) and their involvement in the synthesis of the ␣ chain. Additional genes needed to synthesize the ␤ and ␥ chain have also been identified (1,18), and most of the biochemical properties of these gene products have been defined (41).…”
mentioning
confidence: 84%
“…Simultaneous production of multiple LOS epitopes is mediated by production of limiting amounts of the LgtA, LgtD, or LgtE. This occurs via transcriptional or translational strand slippage (11), via regulation of transcriptional expression (the present study), and via the low kinetic efficiencies of specific glycosyl transferases (36). In addition, recombination between glycosyl transferases is seen in some strains of Neisseria and these recombinant loci may consequently invoke one or more of the above mechanisms of phase variation (5,36 …”
Section: Discussionmentioning
confidence: 73%
“…The resulting strain was termed LPS1. Five glycosyltransferase genes necessary for the display of the Lewis Y antigen from different bacterial sources were expressed heterologously: lgtE, encoding a β1,4-galactosyltransferase of Neisseria gonorrhoea reported to transfer to glucose in the LOS structure of N. gonorrhoea [31]; lgtA from Neisseria meningitidis encoding a β1,3-N-acetylglucosaminyltranferase with galactose as an acceptor, and lgtB, encoding a β1,3-galactosyltranferase with N-acetylglucosamine as an acceptor, also from N. meningitidis [32]. In addition, futA and futC, encoding α1,3-and α1,2- (Fig.…”
Section: Resultsmentioning
confidence: 99%